Analysis of The Quality of Inpatient Services from The Patient's Perspective at Bima Regional General Hospital - Nurwahidah, .; Sastrawan, .; Sulaiman, Lalu (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2024)
The problem raised in this research is the lack of patient satisfaction when being treated at Bima Hospital. According to data on the number of customer complaints regarding the quality of service at Bima Hospital in 2021, there were 1281 complaints, including: 454 (35.4%) complaints inpatient wards, 295 (23%) in outpatient, Emergency Rooms were 289 (22.6%). %), Radiology was 123 (9.6%), Pharmacy was 45 (3.5%), 44 (3.4%) complaints in Nutrition unit, and 35 (2.7%) complaints in other units. This is what influences patient satisfaction regarding the services provided by the hospital. Patient satisfaction is a big challenge in providing health services today. This research is a descriptive analytical research using a quantitative approach. With a cross-sectional study research design. This study aims to measure the quality of health services from the patient's perspective while being treated in hospital, analyzing data for descriptive hypothesis testing using the t-test. The research sample consisting of 97 inpatient patients chosen using Simple Random Sampling. T-test results showed that the Std.Deviation of 9.115 expectations was smaller than the Std.Deviation of 20.265 of reality. Therefore, from the results of the t-test test with a p value of 0.000 could be concluded that there was a difference between expectations and the reality that was accepted in review the score given by the patient. The level of conformity to the results of this research shows that many patients feel that the quality of service provided by the Bima Regional Hospital is very much in line with their expectations.